Integral representations at the boundary for Stokes flow and related symmetric Galerkin formulation (Archives of Mechanics - Test, 2005)
A symmetric Galerkin boundary element formulation is given for the first time for two-dimensional, steady and incompressible flow. The formulation requires the derivation of certain integral representations (whose importance extends beyond the present application) for velocity gradient and pressure at the flow boundary; these turn out to be coupled at angular points of the contour profile.